Bringing Indigenous Voices to the Workplace - Hunt, Jaydum (University of Waterloo, 2021)
Abstract I question how Indigenous identity, relationships, and the workplace environment affect an Indigenous employee’s experience in the workplace. I had the pleasure and opportunity of hearing and now sharing the stories of seven Indigenous alumni from the University of Waterloo and Wilfred Laurier University, who live and work in southwestern Ontario. Research shows that Indigenous employees are unsatisfied, have a high attrition rate, and lack representation within the workplace (Hsiao, Auld & Ma, 2014; Liao, Chuang, & Joshi, 2008; Racine, 2016; Scott, Heathcote & Gruman, 2011). My research aimed to understand the sources of satisfaction and retention for Indigenous employees within the workplace. To do this, I had conversations about their experiences within the organizations that they work. The themes discussed in the conversations covered cultural identity, workplace relationships, communication, and workplace environment. The first theme surrounding identity comes from my journey surrounding my indigeneity , my changing identity, and the impact it has had on my experience throughout life, in school, and within the workplace. The second theme, communication, comes from the understanding that communication is a part of every organizational process and is related to task performance, job satisfaction, and trust. (Adair, Buchan, Chen, & Liu, 2016). The third theme, relationships, is a big part of the workplace experience for both Indigenous and non-Indigenous people (Burgess & Dyer, 2009; Venkataramani, Labianca, & Grosser, 2013). The fourth and final theme, the workplace environment, is taken into consideration as it is another large part of the experience of Indigenous employees within the workplace. In order to have a full understanding of the experience of an Indigenous employee, it was necessary to use Indigenous research methods. I had four relational conversations with each participant that ranged from 45 minutes to an hour in length and took place in the majority of my ...